2019
DOI: 10.1186/s13046-019-1476-5
|View full text |Cite
|
Sign up to set email alerts
|

N-myc downstream-regulated gene 1 inhibits the proliferation of colorectal cancer through emulative antagonizing NEDD4-mediated ubiquitylation of p21

Abstract: BackgroundN-myc downstream-regulated gene 1 (NDRG1) has been shown to play a key role in tumor metastasis. Recent studies demonstrate that NDRG1 can suppress tumor growth and is related to tumor proliferation; however, the mechanisms underlying these effects remain obscure.MethodsImmunohistochemistry (IHC) was used to detect NDRG1 and p21 protein expression in colorectal cancer tissue, and clinical significance of NDRG1 was also analyzed. CCK-8 assay, colony formation assay, flow cytometry, and xenograft model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
(76 reference statements)
0
26
0
Order By: Relevance
“…NEDD4 could target p21 protein for degradation by increasing the ubiquitylation of p21, and promote cell proliferation. N-myc downstream-regulated gene 1 (NDRG1) inhibits colorectal cancer cell proliferation through emulatively antagonizing NEDD4-mediated ubiquitylation of p21, which suggests an oncogenic role of NEDD4 in colorectal cancer ( 14 ). In malignant glioma, researchers found that NEDD4 directly promotes cell migration and invasion, but does not affect the proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…NEDD4 could target p21 protein for degradation by increasing the ubiquitylation of p21, and promote cell proliferation. N-myc downstream-regulated gene 1 (NDRG1) inhibits colorectal cancer cell proliferation through emulatively antagonizing NEDD4-mediated ubiquitylation of p21, which suggests an oncogenic role of NEDD4 in colorectal cancer ( 14 ). In malignant glioma, researchers found that NEDD4 directly promotes cell migration and invasion, but does not affect the proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…NDRG1 is the most significantly affected gene of the validated candidates. Interestingly, NDRG1 was previously shown to be a metastasis suppressor and is highly downregulated in colorectal cancer [61,62]. Furthermore, we found several regulated genes belonging to the group of the ISGylation pathway, which is important for ISG15 conjugation [64,65].…”
Section: Protein Coding Gene Expression Analyses Identify Several Immmentioning
confidence: 65%
“…NDRG1 is the most significantly affected gene of the validated candidates. Interestingly, NDRG1 was previously shown to be a metastasis suppressor and is highly downregulated in colorectal cancer [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…HMGCS1 is upregulated in prostate cancer, and the knockdown of this gene inhibits cell viability in 22Rv1 cells [ 36 ]. NDRG1 has been reported as a tumor suppressor decreasing in colorectal cancer inhibits tumor proliferation through increasing p21 stability [ 37 ]. MVD is involved in mevalonate pathway for cholesterol biosynthesis but the role of this gene is not clear in tumors.…”
Section: Discussionmentioning
confidence: 99%